Direct Graphene Synthesis on Lithium Niobate Substrate by Carbon Ion Implantation - Xu, Yuhang; Lu, Fei; Liu, Kaijing; Ma, Changdong (Frontiers in Materials, 2020)
For this study, a dozen-micron-scale four to seven layers of graphene were synthesized directly onto Lithium Niobate (LiNbO3, LN) by carbon implantation in a nickel covered LiNbO3 film. The 1.52E16 ions·cm−2 carbon ions of 80 keV were implanted into the nickel film to a depth of 100 nm, which is close to the interface between the nickel film and the LiNbO3. The implanted carbon atoms dissolved in nickel at an elevated temperature and diffused towards the interface between the nickel film and LiNbO3 during annealing. After the nickel film fell off, the graphene material was found by Raman spectroscopy and confirmed by the Atomic Force Microscope topographic image. This implantation combined with patterned metal film suggests possibilities for engineering two-dimensional graphene with special confinement. It also provides a valuable and novel way for integrating graphene-wafer structure for other available substrate wafer in microelectronics and photonics devices.